The business plan - Taylor, Suzi; Video Education Australasia (Bendigo, Vic. : Video Education Australasia, 2009)
This program spotlights two very different small-business owners--a physical therapist and a performance artist--who have something very important in common: a business plan. Over the course of the video, Peter Dolan and Neda Rahmani talk about the key components of a business plan: the executive summary and overview, the operations plan, the marketing plan, and the financial plan. Expert commentary is provided by Nicole Donegan, a business growth adviser with 20 years' experience in B2B and professional services marketing'
Executive producer, Simon Garner
Voice over: Carly Schrever
DVD format
Keywords: Business planning; Strategic planning; Small business -- Management -- Case studie; Small business marketing